Consular Law Trends - O. M. Torshina (Московский журнал международного права, 2009)
Over time, the range of issues within the competence of consular institutions has been steadily expanding, and their functions have increasingly become more and more comprehensive. Nowadays, consular institutions are designed to facilitate development not only of economic and business but also scientific, technical, cultural, and in some instances political ties between states. Consular relations are a type of international relations which are primarily established to protect states, the rights and legitimate interests of their citizens and legal entities that happen to be or act in the territory of other countries. Recently, in the course of consular treaty practice, international legal principles have been formed to regulate establishment and performance of consular relations and functions. They can be divided into two groups: 1) general principles of international law and 2) branch (specialized) principles of consular law.